Shopping revolution : how retailers succeed in an era of endless disruption accelerated by COVID-19 - Kahn, Barbara E. (Wharton School Press, 2021)
The retail industry was already in the midst of unparalleled disruption. They came COVID-19. In a fully updated and expanded edition of The Shopping Revolution, Wharton professor Barbara E. Kahn examines the companies that have been most successful during a tsunami of change in the industry. --